Análise das capacidades da tecnologia de informação na Maturidade do gerenciamento de projetos. - Ramos, Ana Caroline Salviano (2016)
The present study aimed to analyze the impact of information technology (IT) capabilities on the maturity of the project management of a power sector company. For the theme comprehension, the study was based on the project management and its areas of knowledge, on project management maturity, on organizational resources, on the dynamic capabilities and IT capabilities. It sought to describe the relationship of IT capabilities with project management with the intention of highlighting the value of IT capabilities in performance for promotion above the level of organizational processes, reflected in the evolution of maturity of the project management and therefore the achievement of a sustained competitive advantage. The research was conducted through an interpretive case study and was guided by a qualitative approach that aimed to identify, through understanding of the stories of the experiences of project managers, the impacts of IT capabilities in the evolution of the maturity of the project management and its areas of knowledge. The research was conducted with ten project managers of a company in the electricity sector which operates in the state of Paraiba and is controlled by a group of companies that operates in the service sector of the Brazilian electric sector. The data collection process came from the knowledge areas of project management, from the project management maturity model (PMMM) and from six categories of IT capabilities: IT business partnerships, external IT linkages, business IT strategic thinking, IT business process integration, IT infrastructure and IT management. The analysis, interpretation and discussion of the results revealed that the IT infrastructure, linkages with external partners IT and integration of business processes and IT were the categories of IT capabilities that impacted the most knowledge areas. The impact of each of these categories of IT capabilities was evident in on least five of the ten knowledge areas studied. Also pointed the reach of the fourth level of maturity MMGP for seven of the ten areas of knowledge. The areas that reached stage four, called managed level were: managing scope, cost, deadlines, communication, risk, quality and integration. But the management of human resources, procurement and stakeholder reached stage three named set or standard level. The main contributions of the studies were: evidence of impacts of IT capabilities in organizational process level and ease in identifying the benefits of IT capabilities, from the process level approach, and contribution to reduction of a gap on the theme. This work indicates directions for future studies that seek to measure the TI impact in process level and studies that address the theme addressed to contribute to reducing the gap of work involving project management and IT capabilities.